HYPOGLYCEMIC ACTIVITY OF A NOVEL POLYHERBAL FORMULATION IN STREPTOZOTOCIN-INDUCED DIABETIC RATS: A THERAPEUTIC STUDY - MAJUMDER, PULAK; M, PARIDHAVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The concept of the synergistic effect of poly-herbalism was as old as medicine history. Present novel polyherbal formulation (PHF) composed of five different herbs. The present investigation aimed to evaluate the synergistic therapeutic hypoglycemic potential of PHF against streptozotocin (STZ) (60 mg/kg b.w, ip)-induced diabetic rats. Methods: For this therapeutic study, the dose was framed orally once a day to the test objects after STZ dosing at 500 mg/kg/5 ml dosage levels for 21 days. The transformation of body weight and blood glucose level was examined, and the histopathological changes of beta cells of the pancreas, cellular architectures of liver and kidney were also perceived after scarification of the objects. Results: The outcomes were compared to that of glibenclamide (5 mg/kg) treated group. Declines of body weight and blood glucose levels were perceived in STZ-induced diabetic animals very significantly (p<0.01 or p<0.05). However, these diabetic changes were significantly (p<0.01 or p<0.05) decreased in PHF-dosing groups revealed more encouraging effects compared to that of glibenclamide. In the other hand, various liver function and enzymes test (creatinine, urea, total bilirubin, total albumin, alkaline phosphatase, gamma-glutamyl transferase, aspartate transaminases, and alanine transaminases) and lipid profile (total cholesterol, triglycerides, high-density lipoprotein cholesterol, total protein, low-density lipoprotein [LDL], and very LDL) studies strongly indicate the potential action of this novel formulation. Conclusions: It is deliberated that PHF has the favorable effect to normalize the blood glucose levels, and also rejuvenation and reproduction of beta cells lead a better futuristic ant diabetic therapy for diabetic management.